First: use distribution by multiplying -2i to everything inside the parenthesis:
(-2i)(5) - (4i)(-2i)
= -10i + 8i^2
Second: the rule is i^2 is -1 and replace i^2 with -1
= -10i +8(-1)
= -10i - 8
2006-12-16 14:03:19
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
-2i(5-4i)=
-10i + 8i^2
Since i^2 = -2, 8i^2 = -8
Rewriting in standard form,
-8 - 10i
2006-12-16 19:32:51
·
answer #2
·
answered by Joni DaNerd 6
·
1⤊
1⤋
2i(5-4i)=10i-8i^2=10i+8=8+10i
2006-12-16 21:48:56
·
answer #3
·
answered by yupchagee 7
·
0⤊
1⤋
-10i +2
2006-12-16 19:31:35
·
answer #4
·
answered by Alan Turing 5
·
0⤊
1⤋
-2i(5-4i)
10i+8i^2
10i+8(-1)
10i-8
-8+10i
2006-12-16 19:35:15
·
answer #5
·
answered by NAchik09 2
·
0⤊
2⤋
hey..i had a very similar question and a math student helped me at http://www.schoolpiggyback.com ...its a similar site to this..but just for students..plus its cool cuz u can make money answering other student's questions....goodluck : )
2006-12-16 19:33:00
·
answer #6
·
answered by lori b 2
·
0⤊
0⤋
-10i+8i*i=-10i-8
2006-12-16 19:39:17
·
answer #7
·
answered by catty 1
·
1⤊
0⤋
-10i-8
-8-10i
2006-12-16 19:35:42
·
answer #8
·
answered by raj 7
·
1⤊
0⤋